2017
DOI: 10.1111/ceo.12958
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of two second‐generation trabecular micro‐bypass stents and topical travoprost in open‐angle glaucoma not controlled on two preoperative medications: 18‐month follow‐up

Abstract: ImportanceAdditional data are sought regarding treatment options for glaucoma, a major cause of global blindness.BackgroundThe study assessed outcomes following standalone implantation of two second‐generation trabecular micro‐bypass stents and postoperative topical prostaglandin in eyes with open‐angle glaucoma not controlled on two preoperative medications.DesignThe study design is a prospective, nonrandomized, open‐label study at a tertiary‐care ophthalmology centre.ParticipantsSubjects had open‐angle glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 21 publications
4
37
1
Order By: Relevance
“…Both groups exhibited nearly 15% medication reduction compared with preoperative medication use. While our study describes a modest IOP and medication reduction following iStent surgery, the extent of IOP and medication changes was not as great as those reported by Lindstrom et al and Berdahl et al, who report a 30%-40% IOP reduction [10,11]. Compared with their studies, our groups had a lower 3 BioMed Research International baseline IOP; it is reasonable that their studies had a higher percent of IOP reduction due to a higher baseline.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Both groups exhibited nearly 15% medication reduction compared with preoperative medication use. While our study describes a modest IOP and medication reduction following iStent surgery, the extent of IOP and medication changes was not as great as those reported by Lindstrom et al and Berdahl et al, who report a 30%-40% IOP reduction [10,11]. Compared with their studies, our groups had a lower 3 BioMed Research International baseline IOP; it is reasonable that their studies had a higher percent of IOP reduction due to a higher baseline.…”
Section: Discussioncontrasting
confidence: 50%
“…Prior studies have evaluated single [3][4][5][6][7][8] and multiple [9][10][11] iStent implantation during cataract surgery in open-angle glaucoma patients. Prospective randomized studies of single stent placement, including those of Samuelson et al [3] (240 eyes), Fea [4] (33 eyes), and Craven et al [5] (240 eyes), found better pressure reduction for patients who underwent cataract surgery with stent implantation, rather than cataract surgery alone, on fewer medications.…”
Section: Discussionmentioning
confidence: 99%
“…The impact on IOP increase of medication washout in eyes with 2 stents has been reported as approximately 4 mmHg. 15,37 Furthermore, a prior report of single versus multiple stent implantation as a stand-alone treatment showed incremental benefit with multiple stents. 23 Neither a comparison of single versus multiple stents nor the stand-alone surgical procedure was in the current study design.…”
Section: Discussionmentioning
confidence: 99%
“…1-2). In studies both with and without cataract surgery, and in both investigational and real-world settings, the ab interno-implanted iStent inject has demonstrated clinically significant reductions in IOP and medications over the long term [40][41][42][43][44][45][46][47][48][49][50][51]. These performance outcomes have been accompanied by favorable safety and a correspondingly advantageous benefit-to-risk profile.…”
Section: Introductionmentioning
confidence: 99%